2005
DOI: 10.1038/oby.2005.50
|View full text |Cite
|
Sign up to set email alerts
|

The Human Obesity Gene Map: The 2004 Update

Abstract: PÉ RUSSE, LOUIS, TUOMO RANKINEN, AAMIR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
170
0
14

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(186 citation statements)
references
References 1,057 publications
(318 reference statements)
2
170
0
14
Order By: Relevance
“…1 Although several obesity quantitative trait loci (QTLs) have been mapped by linkage analysis, identification of underlying susceptibility genes shows slow progress. 2 Recently, genome-wide association studies have identified INSIG2 and FTO as primary obesity genes. 3,4 The association with INSIG2 has not been confirmed in all subsequent studies.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although several obesity quantitative trait loci (QTLs) have been mapped by linkage analysis, identification of underlying susceptibility genes shows slow progress. 2 Recently, genome-wide association studies have identified INSIG2 and FTO as primary obesity genes. 3,4 The association with INSIG2 has not been confirmed in all subsequent studies.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Numerous molecular studies have been launched to search for genetic determinants underlying the variations of obesity-related phenotypes, involving more than 600 genes, markers and chromosomal regions. 6 The CYP19A1 gene encodes the aromatase, an enzyme that catalyses the conversions of C19 androgens, androstenedione and testosterone, to C18 estrogens, estrone and estradiol, respectively. [7][8][9] Testosterone inhibits preadipocyte proliferation and differentiation, 10,11 whereas estradiol appears to stimulate them.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The gene encoding ERRa (ESRRA) is located on chromosome 11q13, a chromosomal region that has shown genetic linkage to body mass index (BMI) and fat percentage. 5,6 A pseudo gene has been identified on chromosome 13q12.1. 7 ESRRA is expressed in several tissues, but most abundantly in tissues with a high capacity for b-oxidation, such as skeletal muscle, heart, kidney, liver and adipose tissue.…”
Section: Introductionmentioning
confidence: 99%